Noise valuation in ex-ante evaluations of major road and railroad projects - Nijland, Hans; Wee, Bert van (European Journal of Transport and Infrastructure Research, 2008)
In many European countries, the impact of new road and railroad infrastructure is assessed by performing a cost-benefit analysis, monetising as many relevant effects as possible. Considering that noise is a major external effect of traffic, this paper will systematically review the guidelines for monetising noise in different European countries. The study shows, firstly, that there are guidelines for monetising noise in most western and northern European countries and secondly, that not all noise effects are dealt with. Usually only annoyance in a residential context is included. Thirdly, the different prices being attached to noise in various countries are mainly due to different unit values applied to the same impacts. Fourthly, a gap has been shown to exist between the theoretical guidelines and their application in practice.